Factors Affecting School Intellectual Quality in Florida - Arbogast, Gordon; Thornton, Barry (Business, Management and Economics: Research Progress Vol. 3, 2024)
This paper examines the factors that are theorized to be determinants of school quality in the 67 counties of Florida from 2000 to 2011. Many of the factors affecting school quality cannot be affected by enacting policies and programs. Economic factors such as county income and economic activity impact school quality, but are unaffected by the decisions made by school boards and school administrators. The model constructed for this purpose is comprised of a mix of independent variables that include county educational attainment (number of high school graduates and State University System enrollees) and economic factors (median household income, unemployment rate, number of housing starts, and property tax revenue per student). Furthermore, the model also considers 4 demographic/social variables (percent of the population from 5 to 17 years old, percent white, percent female, and crime rate), as well as a variable for trend. The trend variable allows inferences to be made about the impact of the No Child Left Behind Act of 2001 (active during the time of the study). It was hypothesized that these 11 variables would explain the variation in school quality by county over the observed time period. The results of the model indicated that the following seven variables had the most impact on intellectual school quality in Florida - high school graduates, State University System Enrollment, % white, housing starts median household income, school age, income, and a variable for trend.